Control de inundaciones en propuesta de diseño de muro de gaviones aplicando metodología BIM. estudio de caso - Baltán Larrosa, Shirley Lizbeth (2024)
Many natural disasters can be mitigated or solved with man-made infrastructure works; river overflows are one of the most common causes of damage in rural sectors. The infrastructure works that are applied to prevent the impacts of river flooding are riverside defenses. In this research project, the proposal for a gabion wall for the Dulcepamba River will be carried out. This engineering solution contributes a lot to the communities because it generates jobs, is friendly to the environment and among other benefits that will be addressed in this document..........